Typical Girls The Rhetoric of Womanhood in Comic Strips - Kirtley, Susan E. (The Ohio State University Press, 2021)
In the years following 1975, a group of female-created comic strips came to national attention in a traditionally male-dominated medium. Typical Girls: The Rhetoric of Womanhood in Comic Strips uncovers the understudied and developing history of these strips, defining and exploring the ramifications of this expression of women's roles at a time of great change in history and in comic art. This impressive, engaging, and timely study illustrates how these comics express the complexities of women's experiences, especially as such experiences were shaped by shifting and often competing notions of womanhood and feminism. Including the comics of Lynn Johnston (For Better or For Worse), Cathy Guisewite (Cathy), Nicole Hollander (Sylvia), Lynda Barry (Ernie Pook's Comeek), Barbara Brandon-Croft (Where I'm Coming From), Alison Bechdel (Dykes to Watch Out For), and Jan Eliot (Stone Soup), Typical Girls is an important history of the representation of womanhood and women's rights in popular comic strips.